Extracorporeal Membrane Oxygenation After Norwood Surgery in Patients With Hypoplastic Left Heart Syndrome: A Retrospective Single-Center Cohort Study From Brazil - Bezerra, Rodrigo Freire; Pacheco, Juliana Torres; Volpatto, Victor Hugo; Franchi, Sônia Meiken; Fitaroni, Rosangela; da Cruz, Denilson Vieira; Castro, Rodrigo Moreira; da Silva, Luciana da Fonseca; da Silva, José Pedro (Frontiers in Pediatrics, 2022)
Background: Extracorporeal membrane oxygenation (ECMO) is increasingly being used to support patients after repair of congenital heart disease. Objective: We report our experience with patients with a single functional ventricle who were supported by ECMO after Norwood procedure, reviewing the outcomes and identifying risk factors for mortality in these patients. Methods: In this single center retrospective cohort study, we enrolled 33 patients with hypoplastic left heart syndrome (HLHS) who received ECMO support after Norwood procedure between January 2015 and December 2019. The independent variables evaluated in this study were demographic, anatomical, and those directly related to ECMO support (ECMO indication, local of initiation, time under support and urinary output while on ECMO). The dependent variable was survival. A p-value <0.05 was considered statistically significant. Results: The ECMO support was applied in 33 patients in a group of 120 patients submitted to Norwood procedure (28%). Aortic atresia was present in 72.7% of patients and mitral atresia in 51.5%. For 15% of patients, ECMO was initiated in the operating room; for all other patients, ECMO was initiated in the intensive care unit. The indications for ECMO in CICU were cardiac arrest in 22 (79%) of patients, low cardiac output state in 10 (36%), and arrhythmia in 1 patient (3.5%). The median time under support was 5 (2-25) days. The median follow-up time was 59 (4-150) days. Global survival to Norwood procedure was 90.9% during the 30-day follow-up, being 45% for those submitted to ECMO. Longer ECMO support (p=0.004) and renal failure (p=0.001) were associated with a higher risk of death in the group submitted to ECMO. Conclusions: The mortality of patients with HLHS who received ECMO support after stage 1 palliation was high. Patients with low urine output were related to worse survival rates and longer periods under ECMO support (more than 9 days of ECMO) was associated with 100% mortality. Earlier ECMO initiation before multiorgan damage may improve results.